058 Does prolonging duration of monitoring in epilepsy monitoring unit improve diagnostic yield?. Issue 9 (12th August 2022) - Adenan, Mohammad Hijaz; Khalil, Mohamed; Loh, Kai Sheng; Shukralla, Arif; Kilbride, Ronan; Mullins, Gerrard; Widdess-Walsh, Peter; Kinney, Michael; Delanty, Norman; El-Naggar, Hany
Abstract : Long-term video electroencephalographic (vEEG) monitoring is a valuable tool in the evaluation of par- oxysmal clinical events. However, vEEG itself is costly. We aimed to establish whether longer duration of monitoring (DOM) is associated with higher diagnostic yield. We performed a retrospective study of 501 patients admitted to the epilepsy monitoring unit for diagnostic evaluation. Overall, 436 (87%) patients had diagnostic studies. Of these, 67.9% patients received diagnosis within the first 7 days of monitoring with the highest during day 7. A total of 175 had DOM >7 days of which 80.1% were diagnostic. In cohort with DOM >7 days, patients with previous abnormal routine EEG, previous vEEG monitoring, earlier first event recorded and more number of events were more likely to have diagnostic studies. The most common reason for DOM >7 days was to capture more events (76%). Our study supports that longer DOM was associated with an increase in diagnostic yield. More than one third of our cohort were monitored beyond 7 days with majority of these (80.1%) were diagnostic. Our findings may guide clinicians in planning DOM and predicting likelihood of diagnostic studies in patients with prolonged DOM based on clinical char- acteristics and vEEG data.